Water, Politics and Society : A look at a major work: Consensus en conflict as seen from France - Morera, Raphaël (TSEG - The Low Countries Journal of Social and Economic History, 2023)
Consensus en conflict takes stock of twenty years of research in Dutch environmental history and at the same time offers fruitful perspectives for the years to come. Since the Middle Ages, wetlands and marshes have been attractive areas for societies seeking to exploit their resources or to cultivate them. In Italy, Spain, England, the Germanic countries and France, impressive amounts of land were conquered from the water, sometimes explicitly inspired by the Dutch example. The works are old and temper the exceptionalist reading long promoted by Dutch historians. However, on the whole, they are oriented towards an understanding of the developments and the modalities of the transformations of the environments. In reality, these historiographies do not really question the daily functioning of the organisations exploiting the hydraulic commons. In this sense, Consensus en Conflict is a valuable source of inspiration and invites us to shift our focus.